SILODOSIN VERSUS TAMSOLIN IN THE MANAGEMENT OF LOWER (DISTAL) URETERIC STONE (The Research of Medical Science Review, 2025)
Objective: To compare the efficacy of Silodosin versus Tamsulosin in the management of lower ureteric stones in terms of stone expulsion rate, time to stone expulsion, pain episodes, analgesic requirement, and adverse effects. Place and Duration of Study: Department of Urology, Sahiwal Teaching Hospital, Sahiwal; conducted over six months following the approval of the synopsis by the College of Physicians and Surgeons Pakistan (CPSP). Study Design: Randomized Controlled Trial. Methodology: A total of 100 patients aged 20–55 years with unilateral lower ureteric stones (5–10 mm) were enrolled using non-probability consecutive sampling. Participants were randomly allocated into two equal groups: Group A received Silodosin 8 mg once daily, while Group B received Tamsulosin 0.4 mg once daily for 14 days. Outcomes assessed included stone expulsion rate, mean time to stone passage, number of pain episodes, analgesic use, and adverse effects. Statistical analyses included t-tests, Chi-square tests, and logistic regression, with a significance threshold of p < 0.05. Results: Stone expulsion was achieved in 90% of patients in the Silodosin group compared to 68% in the Tamsulosin group (p = 0.004; OR = 4.2, 95% CI: 1.412.3). Mean expulsion time was significantly lower in the Silodosin group (8.6 ± 2.2 days vs. 12.1 ± 3.1 days; p < 0.001). Pain episodes and analgesic use were also lower in the Silodosin group (p = 0.002 and p = 0.01, respectively). Retrograde ejaculation was more common with Silodosin (18% vs. 8%), though all events were self-limiting. Conclusion: Silodosin demonstrated superior efficacy over Tamsulosin in facilitating lower ureteric stone expulsion, with faster clearance and fewer symptoms. It may be considered a more effective medical expulsive therapy in resource-limited settings like Pakistan.